Pulmonary neuroendocrine neoplasms with well differentiated morphology and high proliferative activity: illustrated by a case series and review of the literature. (December 2020) - Hermans, B.C.M.; Derks, J.L.; Moonen, L.; Habraken, C.H.J.; der Thüsen, J. von; Hillen, L.M.; Speel, E.J.M.; Dingemans, A-M.C.
Highlights: Carcinoids are characterized by well differentiated morphology and low proliferation. LCNEC is characterized by poorly differentiated morphology and high proliferation. We identified 7 pulmonary NEN with high proliferation but preserved differentiation. pRb expression might be useful in this subgroup as a classifying or prognostic marker. Abstract: Objectives: Pulmonary neuroendocrine neoplasms (NENs) are subdivided in carcinoids and neuroendocrine carcinomas (small cell lung carcinoma and large cell neuroendocrine carcinoma (LCNEC)), based on the presence of necrosis and mitotic index (MI). However, it is unclear if tumors with well differentiated morphology but high proliferation rate should be regarded as LCNEC or as high grade carcinoids. In previous case series, a longer overall survival then expected in LCNEC has been suggested. We describe 7 of those cases analyzed for pRb expression and overall survival. Material and methods: Cases with well differentiated morphology, but MI > 10/2mm 2 and/or Ki-67 proliferation index >20% were selected based on pathology reports of consecutive NENs in our university medical center (Maastricht UMC+, 2007-2018) and confirmed by pathological review. Immunohistochemistry was performed to assess pRb expression. Results: Seven stage IV cases were included in this study. Median overall survival was 8 months (95% confidence interval 5-11 months). Cases with well differentiated morphology and preserved pRb expression (4/7) had a median overall survival of 45 months. Conclusion: A subgroup of pulmonary NENs with well differentiated morphology but high proliferation rate likely exists. pRb staining might be helpful to predict prognosis, but clinical relevance remains to be studied.